(NrASSKAVI MNE O MOREs - (N|LX^IN sAFARLIs (Moscow (NiZDATELXSTWO asts, 2018)
(NwY KOGDA(B-(NNIBUDX ZAME^ALI(B, (N^TO GOROD (B- (NKAK L@BIMYJ ^ELOWEK(B? (NoN SLY[IT TEBQ(B, (NZABOTITSQ O TEBE(B, (NDELITSQ S TOBOJ(B, (NI TY OTDAE[X EMU TO(B, (N^TO U TEBQ ESTX(B, (NNE ZADUMYWAQSX(B, (NBOLX[E ILI MENX[E(B. (Ni S GORODOM S \TIM(B, (NKAK S L@BIMYM ^ELOWEKOM(B, (NU TEBQ OTNO[ENIQ(B. (NsO WZLETAMI(B, (NSPADAMI I(B, (NSLU^AETSQ(B, (NRAZO^AROWANIQMI(B. (NkONTRASTY(B. (NnO KAKIMI BY ONI NI BYLI(B, (NNAMNOGO WAVNEE TO(B, (N^TO NA GLUBINE(B, (NPOD PEREMEN^IWYM TE^ENIEM MORQ(B. (Ntam l`bowx(B.s
Keywords: Fiction; Romance; Love; Adult Fiction